Final Lengthening and vowel length in 25 languages. (September 2022) - Paschen, Ludger; Fuchs, Susanne; Seifart, Frank
Highlights: A cross-linguistic perspective on Final Lengthening is offered, with data from 25 small and endangered languages. Final Lengthening is a common cross-linguistic phenomenon with considerable variation in scope and degree. Final Lengthening interacts with phonological vowel length in intricate ways. No evidence of Final Lengthening causing neutralization of a phonological vowel length contrast was found. Abstract: Lengthening of segments at the end of prosodic domains is commonly considered a universal phenomenon, but language-specific variation has also been reported, specifically in languages with a phonological vowel length contrast. This cross-linguistic study uses spontaneous speech data from the DoReCo corpus as a testbed to investigate Final Lengthening (FL) in a diverse sample of 25 mostly understudied languages, thirteen of which have a phonological vowel length contrast. The duration of vowels was labeled using an automatic aligner, with additional manual corrections of word boundaries upon which refined segment alignments were created. The study reveals that (i) FL is a widespread process across languages; (ii) FL shows a wide variety of manifestations with respect to the degree and scope of lengthening; (iii) there are several significant interactions between phonological length and positional lengthening. These results lend support to theories assuming a phonological nature of Final Lengthening.